IDH mutations predict longer survival and response to temozolomide in secondary glioblastoma - SongTao, Qi; Lei, Yu; Si, Gui; YanQing, Ding; HuiXia, Han; XueLin, Zhang; LanXiao, Wu; Fei, Yao (Cancer science, 2012)
Recent studies have shown that isocitrate dehydrogenase1/2 (IDH1/2) mutations occur frequently in secondary glioblastoma. This study aimed to investigate their impact on temozolomide chemosensitivity and relationship with O(6)‐methylguanine DNA methyltransferase (MGMT) promoter methylation in secondary glioblastoma. Searches for IDH1 and IDH2 mutations, 1p19q codeletion, MGMT promoter methylation, and p53 expression were carried out in a series of 86 secondary glioblastomas and correlated with progression‐free survival and overall survival. Response to temozolomide was evaluated by progression‐free survival, as well as by tumor size on successive MRI scans, then correlated with molecular alterations. IDH (IDH1 or IDH2) mutations were found in 58/79 patients (73.4%). IDH mutation, MGMT promoter methylation, and 1p19q codeletion were associated with prolonged progression‐free survival in univariate (P < 0.001, P < 0.001, P = 0.003, respectively) and multivariate analysis (P < 0.001, P < 0.001, P = 0.035, respectively). IDH mutation (P = 0.001) and MGMT promoter methylation (P = 0.011) were correlated with a higher rate of objective response to temozolomide. Further analysis of response to temozolomide showed that patients with both IDH mutation and MGMT promoter methylation had the best response rate to temozolomide. IDH mutation appears to be a significant marker of positive chemosensitivity in secondary glioblastoma. Use of IDH status combined with MGMT promoter status as a stratification factor seems appropriate in future clinical trials involving temozolomide for the treatment of patients with secondary glioblastoma. (Cancer Sci 2012; 103: 269–273)